Solar-driven formic acid continuous hydrogen production system and method
By combining the photothermal conversion-catalytic layer of the supported catalyst in the pores of melamine carbide foam, the gas-liquid phase transformation of formic acid is achieved, and the problems of mass transfer resistance and heat loss in photothermal catalytic hydrogen production are solved, and the production of improved Hydrogen efficiency and reduces costs.
Patent Information
- Application Number
- CN202411429208.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-03
AI Technical Summary
The existing photothermal catalytic hydrogen production technology is affected by the catalyst band gap limitation, heat loss and mass transfer resistance, resulting in low hydrogen production efficiency and high catalyst recovery cost.
Using solar-powered formic acid continuous hydrogen production system, the photothermal conversion-catalytic layer is formed by loading catalysts in the pores of melamine carbide foam, and combined with the liquid transport layer, and the interface between the photothermal conversion-catalytic layer and the liquid transport layer is realized. Gas-liquid phase transformation reduces mass transfer resistance and improves photothermal conversion efficiency.
It significantly improves the hydrogen production efficiency, expands the light absorption range of solar energy, reduces light and heat loss, avoids catalyst deactivation and excess recovery steps, and reduces application costs.
Smart Images

Figure CN119236840A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photothermal catalytic hydrogen production, and in particular relates to a solar-driven formic acid continuous hydrogen production system and method. Background Art
[0002] At present, solar-driven hydrogen production focuses on photocatalytic hydrogen production, including photocatalytic water decomposition, formic acid decomposition and other methods. However, photocatalysis is limited by the band gap of the catalyst and cannot realize the utilization of the full spectrum of solar energy, which limits the rate of hydrogen production. In addition, formic acid hydrogen production focuses on the study of thermal catalysis, and photothermal catalytic hydrogen production is also limited to directly putting the catalyst into the reaction solution, resulting in great heat loss and limiting the hydrogen production performance. At the same time, as a hydrogen storage medium, the hydrogen production rate of formic acid is limited by the degree of ionization and requires additional catalysts, resulting in a decrease in hydrogen storage density and an increase in application costs. In addition, the densely stacked catalysts in the current formic acid hydrogen production system produce huge mass transfer resistance, which also limits the hydrogen production rate. Summary of the invention
[0003] In order to overcome the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a solar-driven formic acid continuous hydrogen production system and method to solve the problem of low hydrogen production efficiency caused by light and heat loss and system resistance.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] In a first aspect, a solar-driven formic acid continuous hydrogen production system is provided, comprising a photothermal conversion-catalytic layer and a liquid transport layer; the photothermal conversion-catalytic layer is disposed on the liquid transport layer; the liquid transport layer is disposed in formic acid;
[0006] The photothermal conversion-catalytic layer is composed of a catalyst loaded in the pores of carbonized melamine foam;
[0007] The liquid transmission layer is melamine foam.
[0008] In one embodiment, the catalyst is Ti 3 C 2 T X .
[0009] In one embodiment, the volumes and densities of the photothermal conversion-catalytic layer and the liquid transport layer are such that when the liquid transport layer is placed in formic acid, the photothermal conversion-catalytic layer can float completely or partially on the liquid surface.
[0010] In one embodiment, the photothermal conversion-catalytic layer is prepared by the following method:
[0011] preparing a catalyst slurry;
[0012] The melamine foam is added into an ethanol solution for ultrasonic cleaning and drying, and then heated to carbonize the melamine foam to obtain carbonized melamine foam;
[0013] The carbonized melamine foam is immersed in the catalyst slurry to absorb the catalyst, and then dried to remove moisture, thereby obtaining the photothermal conversion-catalytic layer.
[0014] In one embodiment, the catalyst slurry is prepared by the following method:
[0015] LiF and HCl were mixed and stirred, and then Ti 3 AlC 2 Stirring at 40°C-50°C to obtain an acidic slurry, washing, and centrifuging until the pH value is 5.5-6.5 to obtain the catalyst slurry; by weight, LiF and Ti 3 AlC 2 The dosage ratio of is (1-1.6):1, and the dosage ratio of HCl to LiF is (0.2-0.3):1.
[0016] In one embodiment, the melamine foam is dried at 60° C.-80° C. after ultrasonic cleaning, and the carbonized melamine foam is dried at 80° C.-100° C. after absorbing the catalyst.
[0017] In one embodiment, the carbonization condition is 500° C.-800° C., 300-500 min.
[0018] In one embodiment, the liquid transport layer is prepared by the following method:
[0019] The melamine foam was added to an ethanol solution for ultrasonic cleaning and dried, and then washed with ethanol several times to obtain a liquid transport layer with uniform pores.
[0020] In one embodiment, the drying conditions are: vacuum drying at 80°C-100°C for 300-500 min.
[0021] In a second aspect, a method for producing hydrogen from formic acid driven by solar energy is provided, which is implemented based on the system for producing hydrogen from formic acid driven by solar energy in the first aspect and comprises the following steps:
[0022] The liquid transport layer is placed in formic acid, and based on gravity, all or part of the photothermal conversion-catalytic layer floats on the liquid surface;
[0023] When the system is placed under light conditions, the temperature difference between the photothermal conversion-catalytic layer and the liquid transport layer causes the formic acid to undergo a gas-liquid phase change. The formic acid is pumped upward through the liquid transport layer, and after the phase change, it diffuses to the photothermal conversion-catalytic layer and adheres to the catalyst surface. The catalyst directly decomposes formic acid to produce hydrogen.
[0024] In one embodiment, the liquid transport layer and / or the photothermal conversion-catalytic layer covers the entire formic acid liquid surface.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention concentrates the catalyst on the photothermal conversion-catalytic layer, expands the light absorption range of solar energy, reduces photothermal loss, pumps formic acid through the liquid transmission layer, and realizes gas-liquid phase change at the interface based on photothermal effect, reduces mass transfer resistance, and ultimately improves the efficiency of photothermal conversion.
[0027] The outdoor experiment of the present invention proves that the final hydrogen production efficiency reaches 200.9mmol g -1 h -1 , compared with the hydrogen production efficiency of directly dissolving the catalyst in formic acid (13.4 mmol g -1 h -1 The above-mentioned solar-driven formic acid continuous hydrogen production system realizes formic acid hydrogen production driven by solar thermal energy, which not only expands the absorption range of solar energy, but also reduces the loss of light and heat, avoids the deactivation of catalyst materials, and realizes the one-step recovery of catalysts, saving unnecessary recovery steps.
[0028] In addition, the entire system has a simple preparation process, a wide range of material sources, and low costs, which will help further promote the technical application of solar thermal hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the hydrogen production system of the present invention.
[0030] Figure 2 It is a schematic diagram of the photothermal conversion-hydrophilicity and hydrophobicity test of the catalytic layer of the present invention.
[0031] Figure 3 It is a schematic diagram of the hydrophilicity and hydrophobicity test of the liquid transport layer of the present invention.
[0032] Figure 4 It is the hydrogen production rate of the hydrogen production system of the present invention under the irradiation of a simulated light source.
[0033] Figure 5 It is a physical picture of an outdoor experiment of an embodiment of the present invention.
[0034] Figure 6 It is the hydrogen production rate of the hydrogen production system of the present invention in outdoor experiments under natural light. DETAILED DESCRIPTION
[0035] The embodiments of the present invention are described in detail below with reference to the accompanying drawings and examples.
[0036] like Figure 1As shown, the present invention is a solar-driven formic acid continuous hydrogen production system, comprising a photothermal conversion-catalytic layer 1 and a liquid transport layer 2. The photothermal conversion-catalytic layer 1 is directly placed on the liquid transport layer 2, and the two are in contact. The liquid transport layer 2 is directly placed in formic acid. The volume and density of the two enable the photothermal conversion-catalytic layer 1 to float completely or partially above the liquid surface.
[0037] The photothermal conversion-catalytic layer 1 of the present invention is composed of a catalyst loaded in the pores of carbonized melamine foam, and the liquid transport layer 2 is melamine foam. The liquid transport layer 2 can use the capillary force of the porous medium of melamine foam to realize the upward transmission of formic acid, and realize the phase change vaporization of formic acid at the contact interface between the photothermal conversion-catalytic layer 1 and the liquid transport layer 2, and then the gaseous formic acid completes catalytic decomposition in the photothermal conversion-catalytic layer 1.
[0038] According to the system structure, the present invention introduces a photothermal conversion-catalytic layer 1 and a liquid transport layer 2. On the one hand, the liquid transport layer 2 is used to pump formic acid to the contact interface between the two layers, and formic acid is converted from liquid phase to gas phase based on photothermal effect to achieve gas-liquid phase change. The diffusion rate of gas-phase formic acid is much higher than that of liquid-phase formic acid and is no longer subject to the diffusion resistance of the solution, thereby reducing the mass transfer resistance. The gas-phase formic acid is decomposed after being catalyzed by the catalyst, thereby avoiding the ionization inhibition of liquid-phase formic acid and the consumption of the catalyst promoter. On the other hand, the catalyst is concentratedly loaded on the photothermal conversion-catalytic layer 1, thereby reducing light loss, improving the efficiency of photothermal conversion, expanding the absorption spectrum of solar energy, and also saving the subsequent catalyst recovery steps, thereby reducing the application cost.
[0039] In the embodiment of the present invention, the catalyst used is still the commonly used catalyst Ti for producing hydrogen from formic acid. 3 C 2 T X In other words, the present invention improves the efficiency of hydrogen production from formic acid by modifying the system rather than the catalyst, thereby reducing the dependence on new materials.
[0040] In an embodiment of the present invention, the photothermal conversion-catalytic layer 1 can be prepared by the following method:
[0041] Step 1, preparing catalyst slurry.
[0042] A feasible method is to mix LiF and HCl and stir for about 15 minutes, then slowly add Ti 3 AlC 2 , continue stirring to obtain an acidic slurry, wash the acidic slurry, centrifuge until the pH value is 5.5-6.5, and obtain a catalyst slurry. 3 AlC 2The dosage ratio of is (1-1.6):1, the dosage ratio of HCl to LiF is (0.2-0.3):1, and the concentration is about 12 mol L -1 about.
[0043] Preferably, Ti is added 3 AlC 2 Then, the system was heated to 40-50°C and stirred to ensure that HCl was 3 AlC 2 The best etching temperature is 48 hours, and the stirring time is about 48 hours. The obtained acidic slurry is washed with deionized water for many times, and then centrifuged at 3500 rpm for 5 minutes until the pH value is 6.
[0044] Step 2: adding the melamine foam into an ethanol solution, ultrasonically cleaning and drying it, and then heating it to carbonize it to obtain carbonized melamine foam.
[0045] In this step, the melamine foam can be cut into the desired shape. For example, in this embodiment, it is cut into 10×10×10mm 3 The small pieces are ultrasonically cleaned in an ethanol solution for about 30 minutes, and then dried at 60°C-80°C. Then they are transferred to a tube furnace and heated for carbonization. The carbonization conditions can be 500°C-800°C for 300-500 minutes.
[0046] Step 3, immersing the carbonized melamine foam in the catalyst slurry to absorb the catalyst, and then drying to remove moisture, thereby obtaining the photothermal conversion-catalytic layer 1.
[0047] In this step, in order to fully absorb the catalyst, the carbonized melamine foam is preferably completely immersed in the slurry. The concentration of the slurry in this embodiment is 10 mg / mL. The slurry is then squeezed and absorbed and placed in a vacuum oven at 80°C-100°C to dry and remove moisture.
[0048] The photothermal conversion-catalytic layer 1 of the present invention exhibits hydrophobic properties, such as Figure 2 shown.
[0049] The liquid transmission layer 2 of the present invention can directly utilize commercial melamine foam, or can be simply prepared by the following method:
[0050] The melamine foam was added to an ethanol solution for ultrasonic cleaning and dried, and then washed with ethanol for several times to obtain a liquid transport layer 2 with uniform pores.
[0051] As before, in this step, the melamine foam can be cut into the desired shape, and preferably the shape is consistent with the shape cut in the previous step 2, that is, it is cut into 10×10×10mm 3The small pieces were then ultrasonically treated with an ethanol solution for about 60 minutes, and then transferred to a tube furnace and vacuum dried at 80°C-100°C for 300-500 minutes. After that, they were washed with ethanol several times to obtain a liquid transport layer 2 with uniform pores.
[0052] The liquid transport layer 2 of the present invention exhibits hydrophilic properties, such as Figure 3 shown.
[0053] The method for producing hydrogen by using the solar energy driven formic acid continuous hydrogen production system of the present invention,
[0054] The liquid transport layer 2 is placed in formic acid, and based on gravity, all or part of the photothermal conversion-catalytic layer 1 floats on the liquid surface. When the system is placed under light conditions, the temperature difference between the photothermal conversion-catalytic layer and the liquid transport layer causes the formic acid to undergo a gas-liquid phase change. The formic acid is pumped upward through the liquid transport layer 2, diffuses to the photothermal conversion-catalytic layer after the phase change and adheres to the catalyst surface. The catalyst directly decomposes the formic acid to produce hydrogen.
[0055] Obviously, in order to collect hydrogen, the formic acid and hydrogen production system of the present invention should be located in a closed catalytic reactor, and it is best to allow the photothermal conversion-catalytic layer 1 to cover the liquid surface.
[0056] The present invention adopts the following method to perform performance test on the solar-driven formic acid continuous hydrogen production system of this embodiment:
[0057] The photothermal conversion-catalytic layer and the liquid transport layer are stacked and placed in a catalytic reactor. Outdoor natural sunlight is used as the only light source, and liquid formic acid is used as the reactant. The gas production port of the catalytic reactor is connected to a hydrogen collection bag, and then the collected gas is injected into a gas chromatograph for testing.
[0058] The following are two specific embodiments of the present invention.
[0059] Comparative Example (Volume Test)
[0060] 3.2 g LiF and 0.96 g HCl (12 mol L -1 ) and stirred for 15 min. Then, 2.00 g Ti 3 AlC 2 Slowly add to the mixed solution. Stir the mixture at 40°C for 48 hours. Wash the resulting acidic slurry with deionized water several times and centrifuge at 3500 rpm for 5 minutes until the pH value is ≈6 to obtain Ti 3 C 2 T X Serum.
[0061] The obtained Ti 3 C 2 T XAfter freeze drying, the powder was obtained and 10 mL of 15 mol L -1 The formic acid solution was added into the reactor, and 10 mg of Ti 3 C 2 T X Catalyst powder was continuously purged with nitrogen for one hour. The reactor was illuminated by a simulated light source with an intensity of 1000 W / m 2 , connect the gas collection bag to collect gas, and inject it into the gas chromatograph to complete the test. The final hydrogen production rate is 13.4mmol g -1 h -1 .
[0062] Example 1 (System Test)
[0063] The comparative example method was used to prepare Ti 3 C 2 T X Serum.
[0064] Cut the melamine foam into 10×10×10mm 3 The small pieces were added to an ethanol solution for ultrasonic cleaning for 30 min and dried (60 ° C), then transferred to a tube furnace and vacuum dried at 500 ° C for 300 min to obtain carbonized melamine foam. 3 C 2 T X solution (10 mg / mL), squeeze out the absorbed slurry and put it into a vacuum oven at 80° C. to remove moisture, and finally obtain the photothermal conversion-catalytic layer 1.
[0065] Cut the melamine foam into 10×10×10mm 3 The melamine foam was then transferred to a tube furnace and vacuum dried at 100°C for 300 minutes. After that, it was washed with ethanol several times to obtain a liquid transport layer 2 with uniform pores.
[0066] See also Figure 1 The photothermal conversion-catalytic layer 1 is placed above the liquid transport layer 2, and then placed in the reactor, and 20 mL of 26 mol L -1 , eliminating H + Ionization suppression limits the reaction concentration. Comparative example (bulk phase test) Formic acid, nitrogen is continuously passed for one hour. A simulated light source is used to provide input energy, a gas collection bag is connected to collect gas, and the gas is injected into a gas chromatograph to complete the test.
[0067] See also Figure 4 , the input energy density of the simulated light source is 500W / m 2 The hydrogen production rate reached 156 mmol g -1 h-1 ; The input energy density of the simulated light source is 1000W / m 2 The hydrogen production rate reached 200.9 mmol g -1 h -1 ; The input energy density of the simulated light source is 1500W / m 2 The hydrogen production rate reached 228.3 mmol g -1 h -1 ; The input energy density of the simulated light source is 2000W / m 2 The hydrogen production rate reached 243.7 mmol g -1 h -1 .
[0068] Example 2 (outdoor test)
[0069] The photothermal conversion-catalytic layer 1 and the liquid transport layer 2 are obtained by the method of Example 1.
[0070] See also Figure 5 The photothermal conversion-catalytic layer 1 is placed above the liquid transport layer 2, and then placed in the reactor, and 20 mL of 26 mol L -1 Formic acid, continuously pass nitrogen for one hour. Close the reactor gas inlet valve, open the gas collection valve, use outdoor natural light to provide input energy, connect the gas collection bag to collect gas, and inject it into the gas chromatograph to complete the test.
[0071] See also Figure 6 The average energy density of outdoor natural light is about 360W / m 2 The final hydrogen production rate reached 109 mmol g -1 h -1 .
[0072] Example 3
[0073] 2g LiF and 0.4g HCl (12mol L -1 ) and stirred for about 15 minutes to make it uniform. Then, 2.00 g of Ti 3 AlC 2 Slowly add to the mixed solution. Stir the mixture at 50°C for about 48 hours. Wash the resulting acidic slurry with deionized water several times and centrifuge at 3500 rpm for about 5 minutes until the pH value is ≈6.5 to obtain Ti 3 C 2 T X Serum.
[0074] Cut the melamine foam into 10×10×10mm 3The small pieces were added to an ethanol solution for ultrasonic cleaning for 30 min and dried (80 ° C), then transferred to a tube furnace and vacuum dried at 800 ° C for 300 min to obtain carbonized melamine foam. 3 C 2 T X solution (10 mg / mL), squeeze out the absorbed slurry and put it into a vacuum oven at 100° C. to remove moisture, and finally obtain the photothermal conversion-catalytic layer 1.
[0075] Cut the melamine foam into 10×10×10mm 3 The melamine foam was then transferred to a tube furnace and vacuum dried at 80°C for about 300 minutes. After that, it was washed with ethanol several times to obtain a liquid transport layer 2 with uniform pores.
[0076] Using the photothermal conversion-catalytic layer 1 and liquid transport layer 2 prepared in this embodiment, the outdoor experiment of Example 2 was carried out, and the hydrogen production rate reached 109 mmol g -1 h -1 .
[0077] Example 4
[0078] 2g LiF and 0.5g HCl (12mol L -1 ) and stirred for about 15 minutes to mix. Then, 1.6 g Ti 3 AlC 2 Slowly add to the mixed solution. Stir the mixture at 45°C for about 48 hours. Wash the resulting acidic slurry with deionized water several times and centrifuge at 3500 rpm for about 5 minutes until the pH value is ≈5.5 to obtain Ti 3 C 2 T X Serum.
[0079] Cut the melamine foam into 10×10×10mm 3 The small pieces were added to an ethanol solution for ultrasonic cleaning for 30 min and dried (70 ° C), then transferred to a tube furnace and vacuum dried at 600 ° C for 400 min to obtain carbonized melamine foam. 3 C 2 T X solution (10 mg / mL), squeeze out the absorbed slurry and put it into a 90° C. vacuum oven to remove moisture, and finally obtain the photothermal conversion-catalytic layer 1.
[0080] Cut the melamine foam into 10×10×10mm 3The melamine foam was then transferred to a tube furnace and vacuum dried at 80°C for about 300 minutes. After that, it was washed with ethanol several times to obtain a liquid transport layer 2 with uniform pores.
[0081] Using the photothermal conversion-catalytic layer 1 and liquid transport layer 2 prepared in this embodiment, the outdoor experiment of Example 2 was carried out, and the average hydrogen production rate reached 109 mmol g -1 h -1 .
[0082] In summary, the present invention achieves the difference in hydrophilicity and hydrophobicity of melamine foam by controlling the calcination temperature, and at the same time, the carbonized melamine foam can obtain excellent light-to-heat conversion ability, and the catalyst is loaded in its porous pores. Under light, the temperature of the catalyst is greatly increased, and the hydrophobicity of the contact interface is used to force formic acid to vaporize, reducing the diffusion resistance. 3 C 2 T X The formic acid is directly decomposed. Ultimately, this system avoids the ionization suppression of liquid formic acid and the consumption of the catalyst promoter, and the diffusion rate of gaseous formic acid is much higher than that of liquid formic acid, which reduces the mass transfer resistance, saves the subsequent catalyst recovery step, and reduces the application cost.
Claims
1. A solar-driven formic acid continuous hydrogen production system, characterized in that: It comprises a photothermal conversion-catalytic layer and a liquid transmission layer; the photothermal conversion-catalytic layer is placed on the liquid transmission layer; the liquid transmission layer is placed in formic acid; The photothermal conversion-catalytic layer is composed of a catalyst loaded in the pores of carbonized melamine foam; The liquid transmission layer is melamine foam.
2. The solar-driven formic acid continuous hydrogen production system according to claim 1 is characterized in that: The catalyst is Ti3C2T X .
3. The solar-driven formic acid continuous hydrogen production system according to claim 1 or 2, characterized in that: The volumes and densities of the photothermal conversion-catalytic layer and the liquid transport layer enable the photothermal conversion-catalytic layer to float completely or partially on the liquid surface when the liquid transport layer is placed in formic acid.
4. The solar-driven formic acid continuous hydrogen production system according to claim 1 or 2, characterized in that: The photothermal conversion-catalytic layer is prepared by the following method: preparing a catalyst slurry; The melamine foam is added into an ethanol solution for ultrasonic cleaning and drying, and then heated to carbonize the melamine foam to obtain carbonized melamine foam; The carbonized melamine foam is immersed in the catalyst slurry to absorb the catalyst, and then dried to remove moisture, thereby obtaining the photothermal conversion-catalytic layer.
5. The solar-driven formic acid continuous hydrogen production system according to claim 3 is characterized in that: The catalyst slurry is prepared by the following method: LiF and HCl are mixed and stirred, and Ti3AlC2 is added and stirred at 40°C-50°C to obtain an acidic slurry, which is then washed and centrifuged until the pH value reaches 5.5-6.5 to obtain the catalyst slurry; By weight, the ratio of LiF to Ti3AlC2 is (1-1.6):1, and the ratio of HCl to LiF is (0.2-0.3):
1.
6. The solar-driven formic acid continuous hydrogen production system according to claim 3 is characterized in that: The melamine foam is dried at 60° C.-80° C. after ultrasonic cleaning, and the carbonized melamine foam is dried at 80° C.-100° C. after absorbing the catalyst.
7. The solar-driven formic acid continuous hydrogen production system according to claim 3 is characterized in that: The carbonization conditions are 500° C.-800° C., 300-500 min.
8. The solar-driven formic acid continuous hydrogen production system according to claim 1, characterized in that: The liquid transport layer is prepared by the following method: The melamine foam was added to an ethanol solution for ultrasonic cleaning and dried, and then washed with ethanol several times to obtain a liquid transport layer with uniform pores.
9. A method for producing hydrogen from formic acid driven by solar energy, which is realized based on the system for producing hydrogen from formic acid driven by solar energy according to any one of claims 1 to 9, characterized in that: The steps include: The liquid transport layer is placed in formic acid, and based on gravity, all or part of the photothermal conversion-catalytic layer floats on the liquid surface; When the system is placed under light conditions, the temperature difference between the photothermal conversion-catalytic layer and the liquid transport layer causes the formic acid to undergo a gas-liquid phase change. The formic acid is pumped upward through the liquid transport layer, and after the phase change, it diffuses to the photothermal conversion-catalytic layer and adheres to the catalyst surface. The catalyst directly decomposes formic acid to produce hydrogen.
10. The method for producing hydrogen from formic acid driven by solar energy according to claim 9, characterized in that: The liquid transport layer and / or the photothermal conversion-catalysis layer covers the entire formic acid liquid surface.
Citation Information
Patent Citations
Floating modular solar photoreactor
CN110844966A
Interface type photocatalytic hydrogen production structure system and construction method thereof
CN111056528A
Interface thermocatalytic system
CN112791670A
Liquid-solid and gas-solid decoupling type photocatalytic water splitting system based on light condensation-photo-thermal coupling and use method of liquid-solid and gas-solid decoupling type photocatalytic water splitting system
CN115055143A
Device and method for producing hydrogen through solar photolysis of water
CN117105171A
